(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2021)
This research aims to generate comprehensive theoretical contributions about the visionary leader’s corporate social responsibility, which contributes to sustainable human development in the scenario of the company Destilerías Unidas, S.A (DUSA), to contribute to knowledge about the phenomenon. It is a qualitative investigation, directed by the interpretive paradigm and method of critical hermeneutics. I applied in-depth interviews to two social actors, managers in the context investigated, which were transcribed, coded and categorized to be interpreted and triangulated from their voices. The return to the social actor and triangulation account for the credibility and legitimacy of knowledge. The findings associate visionary leadership with the sense and meaning that social actors attribute to the perspective of spontaneous future, projection of ethics on social responsibility (SR), participatory politics, change of mission and vision, making the future from planning and the value of the experiences developed. Reflectively, I conclude that a socially responsible orientation in the organization contributes to the emergence of a participatory visionary leadership with a vision to plan the social and business future.